(untitled) (Contemporary Journal of Social Science Review, 2025)
The psychological well-being of teachers is critical to ensuring the quality of education and student achievement. However, the psychological distress of teachers by geographical area is not the same since it varies according to specific socio-environmental and occupational causes of stress. This study aims to compare depression and anxiety symptoms prevalence and intensity between secondary school teachers in urban and rural settings. A cross-sectional comparative design was employed with a sample of 200 teachers (100 urban, 100 rural) randomly stratified. The degree of psychological distress was assessed by the Depression, Anxiety, and Stress Scale (DASS-21). Independent sample t-tests and regression models showed that teachers in the urban area had significantly higher levels of anxiety due to workload and administrative pressure. In contrast, rural teachers presented higher depressive symptoms due to professional loneliness and scarcity of resources. The findings of the study emphasise the necessity of mental health interventions targeting the specific difficulties faced by teachers working in different learning contexts. The study contributes to the occupational stress literature of teachers and emphasises the relevance of workplace mental health programs. Longitudinal trends and intervention effectiveness should be examined in future studies to minimize psychological distress among teachers.